The Peculiarities of Teaching Foreign Languages by Means of Information and Communication Technologies - Anna Shevchuk (Educational Challenges)
The paper investigates the peculiarities of teaching foreign languages by means of Information and Communication Technologies (ICT). In the course of a comprehensive study the most effective for the development of students’ linguistic and communicative competence, the following types of ICT were singled out and analysed: Internet-based project work, online correspondence by e-mail, chat, blogs, wikis and podcasts and training programs.